Sinkronisasi Hukum Adat Minangkabau Dalam Penerapan Pendaftaran Tanah Sistematis Lengkap - Putri Nabilah Elkas; Rosmidah Rosmidah; Muhammad Amin Qodri (Universitas Cokroaminoto Yogyakarta, 2026)
The Complete Systematic Land Registration Program (PTSL), which is a program initiated by President Jokowi, faces various obstacles in its implementation, especially in customary regions of Minangkabau, the registration of ulayat land. Minangkabau customary law considers land categorized as Harta pusako tinggi to be indivisible and non-transferable to others. The realization of the complete systematic land registration requires complex requirements, such as genealogical records (ranji) or full agreement from all members of the clan (kaum). For issuing land certificates of pusako tinggi, there is a mandatory rule requiring the inclusion of a ranji or clan genealogy listing the names of clan members covering four generations. In Minangkabau, the preparation of a ranji or genealogy must include at least five levels (upward and downward) from the applicant, and not a single clan member may be omitted. This research is a normative legal study that employs a statutory approach and a case approach.